2019
DOI: 10.1080/16549716.2019.1588513
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting low coverage of the vitamin A supplementation program among young children admitted in an urban diarrheal treatment facility in Bangladesh

Abstract: Background: Vitamin A deficiency (VAD) is one of the most prevalent micronutrient deficiencies in the world. About 2% of all deaths among children under five years of age (U-5) are attributable to VAD. Currently evidence-based knowledge is grossly lacking about the factors associated with low coverage of VAS. Objective: This study aims to determine the factors affecting low coverage of the vitamin A supplementation program among the young children admitted to a diarrheal hospital. Methods: We extracted data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…It could be because a higher educated parent in an urban area remains busy with other activities except for their parenting task. Therefore, parents’ awareness of their children may be more effective in reducing the VAD burden [ 20 , 25 ]. The educated parents’ having enough knowledge about vitamin A-rich food also plays a crucial factor in preventing the vitamin A deficiency of their offspring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be because a higher educated parent in an urban area remains busy with other activities except for their parenting task. Therefore, parents’ awareness of their children may be more effective in reducing the VAD burden [ 20 , 25 ]. The educated parents’ having enough knowledge about vitamin A-rich food also plays a crucial factor in preventing the vitamin A deficiency of their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Xerophthalmia among preschool children amounts to about 5 million cases, 10% of which can potentially lead to blindness in India [ 18 , 19 ]. Globally, about 30% of children under the age of 5 years are vitamin A deficient, and about 2% of all deaths are attributable to VAD in this age group [ 14 , 20 ]. The most important agenda of Sustainable Development Goal-3 is to reduce the preventable deaths of under-five children at least as low as 25 per 1000 live births within 2030 [ 21 ] and reduce the number of stunted children under five by 40% by 2025 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh, one study noted that children’s age, religious status, parental education, wealth index, and breastfeeding status were significantly associated with VAS [ 21 ]. Another study reported that parents with no education and low socioeconomic status were less likely to consume VAS for their children [ 7 , 22 , 23 ]. Imdad et al [ 24 ] and Mayo et al [ 25 ] suggested that regular VAS resulted in a 24 to 28% reduction in mortality and a decrease in the incidence of night blindness.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, against the RDA of 300 RE requirement per children per day of under 5 years age consumption is 270 retinol equivalents (RE) of vitamin A. Women of childbearing age is intakes 372RE vitamin A whereas the RDA is 700RE [2]. Adults aging over 18 (considering average body weight of 60Kg for male and 50Kg for female) require 600µg/day vitamin A [3].…”
Section: Introductionmentioning
confidence: 99%